Роль ротового дыхания, в возникновении зубочелюстно-лицевых аномалий и деформаций, нарушении сроков формирования соматического и психического развития ортодонтических пациентов - Аблязов, А.Р.; Сысоев, Н.П.; Зубкова, Л.П. (Таврический медико-биологический вестник, 2011)
On the basis of the spent clinical and functional methods of researches, from 100 orthodontic patients
surveyed by us, at the age from six till seventeen years with anomalies of a bite, at carrying out of functional
respiratory test, tests on a delay of breath after the maximum breath (test to the Bar) or after the maximum
exhalation (test of Gencha) it has been defined that the mixed type of breath is revealed at 78 of 100, and oral
at 22 patients. At 67 patients with sagittal anomalies of a bite time of a delay of breath for a breath is less than
norm: at distal bite it makes (22,77-24,32) seconds, at mezial bite – (19,6 – 20,3) seconds. On an exhalation
this indicator is equal at distal bite (13,9 – 14,5) seconds, at mezial bite – (11,1-11,8) seconds. Р ≤ 0,5. На підставі проведених клінічних і функціональних методів досліджень, з 100 обстежених нами
ортодонтиних пацієнтів, у віці від шести до сімнадцяти років з аномаліями прикусу, при проведенні
функціональної дихальної проби, проб на затримку подиху після максимального вдиху ( проба Штанге
) або після максимального видиху ( проба Генча ) було визначено, що змішаний тип подиху виявлений
в 78 з 100, а ротовий в 22-х пацієнтів. В 67 хворих із сагіттальними аномаліями прикусу час затримки
подиху на вдиху менше норми : при дистальному прикусі воно становить (22,77-24,32) сек, при
мезіальном прикусі - (19,6 - 20,3) сек. На видиху цей показник дорівнює при дистальному прикусі (13,9
- 14,5) сек, при мезіальном прикусі - (11,1-11,8) сек. Р ≤ 0,5.